First observation of coherence in a highly charged ion. (July 2015) - Tashenov, S; Banaś, D; Beyer, H; Brandau, C; Fritzsche, S; Gumberidze, A; Hagmann, S; Hillenbrand, P-M; Jörg, H; Kojouharov, I; Kozhuharov, Ch; Lestinsky, M; et al.
Synopsis: We report the first observation of correlated x rays emitted by a heavy highly charged ion such as hydrogenlike uranium in the process of radiative recombination. The angular correlations between these x rays for the first time revealed a coherence of the populated state in this ion. The results also indicate a strong contribution of the spin-orbit interaction in radiative recombination.